Integration and Productivity: Satellite-Tracked Evidence - Natividad, Gabriel (Management Science, 2014)
This paper introduces satellite-tracked real-time data from a large fishing firm managing its vertically, horizontally, and geographically linked ships to study the causal impact of integration on total factor productivity (TFP) after the firm acquired its vertically unintegrated contractual fish suppliers. TFP increased 16% among newly integrated ships, whereas it did not vary for already owned ships. Some classic mechanisms such as increased effort due to monitoring do not systematically explain TFP gains under integration, whereas evidence on hold-up threat alleviation is mixed. Importantly, enhanced knowledge transfer and hierarchical authority enacting productivity-improving operational practices among newly integrated ships are more likely explanations of the results. This paper was accepted by Bruno Cassiman, business strategy.